Moment sztuki w nauczaniu literatury = The factor of art in teaching literature - Nowakowski, Jan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author underlines the creative factor (root) as essential for the process of teaching in general, a factor which often comes near to art, what confirms the expression appearing in pedagogical literature: "The Art of Teaching". This value is a derivation (function) of the teacher's individuality, whereas this individuality is the fundamental factor in pedagogical influence as well as in the very didactic process.
Keywords: literatura polska - nauczanie